Draft genome sequence data of maqui (Aristotelia chilensis) and identification of SSR markers - Adriana Bastías; Francisco Correa; Pamela Rojas; Constanza Martin; Jorge Pérez-Diaz; Cristian Yáñez; Mara Cuevas; Ricardo Verdugo; Boris Sagredo (Data in Brief, 2019)
Maqui (Aristotelia chilensis [Molina] Stunz) is a small dioecious tree, belonging to the Elaeocarpaceae family. Maqui fruit has high levels of antioxidant activity, which are due to elevated anthocyanin and polyphenol content. Here we describe a draft genome sequence data of maqui (A. chilensis). The genomic sequence datasets were obtained using Illumina NextSeq platform. Nucleotide sequences of raw reads and the assembled draft genome are available at NCBI's Sequence Read Archive as BioProject PRJNA544858. Also, a total of 210067 microsatellite or simple sequence repeat (SSR) markers were identified. Keywords: Maqui, Aristotelia chilensis, Draft genome, Sequencing, Illumina NextSeq platform, SSR markers, Microsatellite